1928
DOI: 10.1037/h0093332
|View full text |Cite
|
Sign up to set email alerts
|

Stanford motor skills unit.

Abstract: The possibility of selecting individuals best suited for training or work in practical motor skills is dependent upon: (1) the adequacy of job analyses, (2) the nature and persistence of individual differences in such skills, and (3) a measuring technique adapted to conditions outside the laboratory.The first step has therefore been an experimental analysis of eight serial motor performances on a group of fifty university men.(9) These tests ranged from speed of discriminative finger movement to accuracy in la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

1931
1931
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…All of these measures were taken in IS minutes and consisted of a total of 240 separate reactions. Other reactions of a very similar nature have been shown to have a high reliability (25,30,12 then the series was begun over again with Y-4, continuing in this manner for 80 exposures. Then a series of 120 exposures was given with no coaching as to the correct finger for each color and a record of the number of correct responses was taken.…”
Section: Mirror-vistonmentioning
confidence: 98%
“…All of these measures were taken in IS minutes and consisted of a total of 240 separate reactions. Other reactions of a very similar nature have been shown to have a high reliability (25,30,12 then the series was begun over again with Y-4, continuing in this manner for 80 exposures. Then a series of 120 exposures was given with no coaching as to the correct finger for each color and a record of the number of correct responses was taken.…”
Section: Mirror-vistonmentioning
confidence: 98%
“…The apparatus used was of the Koerth Pursuit Rotor type (18,20) Essentially this consisted of an electrically driven hard rubber turntable 12 inches in diameter which had a brass target Yz inch in diameter embedded flush with the surface of the turntable near the edge The subject pursued the target by keeping a metal pointer on it The handle of the pointer was hinged so that pressure could not be exerted on the target The turntable rotated at a speed of one revolution per second Full speed of the turntable was attained in one revolution from a stationary starting position Continuous contact of the pointer with the target completed an electric circuit, through ten commutator bars equally spaced on the periphery of the turntable, to an electrical counter which recorded a score of ten per revolution of the turntable A trial consisted of ten revolutions Thus a score of 100 would indicate perfect pursuit Ten trials of ten revolutions each were taken every experimental period The task involved integrating visual pursuit of the rotating target with the proper arm pursuit movement For co-operative subjects the task was interesting and challenging, motivating them highly to do their best, and improvement usually occurred from trial to trial R ESULTS / Achievement (a) Penod I Table II presents the results for Period I, trialby-trial The group of 122 schizophrenic patients has the lowest 'The instructions read to the subject were "On this device you show your abihty to leam a new movement Hold the pointer like this [The subject is shown that the pointer handle is held m the hand with the palm downward and with the fingers around the handle and not touching the movable metal parts ] With the wrist and pointer in a straight line, your body erect and well balanced, keep the pointer on the target as it turns around If you let the pointer get off the target, catch up with the target again, moving the pointer steadily until you get on It At first you may not be able to keep the pointer on the target well, but as you continue your eye and hand will begin to work together and you will improve much if you do your best Your score will be higher the more you make contact with the target Let the other hand rest lightly on the edge of the turntable box If you relax between tnals you will do better When I say, 'Ready,' place the pointer on the target and follow it as best you can until I say, 'Stop'" Each trial began with the turntable in such a position that the target was nearest the subject A rest period of 20 seconds was given between trials scores On the first trial the mean of this group is 16 8, and on the tenth trial the mean is 22 7, an increase of 5 9 The manic-depressive group has a mean of 37 8 on the first trial and achieves 48 9 on the tenth trial, an improvement of 11 1 The normal group begins with a mean of 30 3 on the first trial and reaches 44 3 on the tenth trial, a gam of 14 0 For the ten trials the mean achievement of the schizophrenic group is 19 7, the manic-depressive group 42 7, and the normal group 38 2 The perfonnance of the normal and manicdepressive groups, tnal-by-trial, and also for the mean of ten trials, IS m each case significantly better statistically than that of the schizophrenic group The manic-depressive group is not, however, significantly better than the normal group The pcMDrer achievement m the schizophrenic group is related both to poorer initial level and to lesser improvement from the first to the tenth trial (b) Retest results Table III presents the retest results Both groups continue to improve in the succeeding periods In Period I the mean score of the patients for the ten trials is 16 7, m Period II 27 6, and m Period III 32 7 The difference bet...…”
mentioning
confidence: 99%
“…While completing this training, R. H. Seashore and Miles collaborated to develop the Stanford Motor Skills Unit ( Hilgard, 1980 ). This apparatus included six tests ( Seashore, 1928 ). ( Seashore, 1928 ).…”
Section: Robert H Seashore and Studies Of The Motormentioning
confidence: 99%
“…This apparatus included six tests ( Seashore, 1928 ). ( Seashore, 1928 ). The Brown Spool Packer test measured speed and accuracy.…”
Section: Robert H Seashore and Studies Of The Motormentioning
confidence: 99%
See 1 more Smart Citation